Deterioro del valor de los activos en época de crisis (2014)
The Global accounting standardization going around the International Accounting Standards and Financial Reporting - IAS and IFRS; imposes the tendency to valuation of assets at fair or market value, as opposed to historical cost traditionally handled. In this dynamic, the recognition of the impairment of assets occurred by internal and external causes, play a determinant role. However extraordinary situations imposed by the occurrence of crisis (economic, ecological, natural or political) can generate pessimistic scenarios that accelerate this deterioration, and perhaps no necessarily correspond with reality. This article presents a reflection about the applicability of the criteria of Impairment in extraordinary times of crisis.